Eurasian Beaver (Castor fiber) Winter Foraging Preferences in Northern Poland—The Role of Woody Vegetation Composition and Anthropopression Level - Jackowiak, Mateusz; Busher, Peter; Krauze-Gryz, Dagny (Animals (Basel), 2020)
We studied beavers’ dietary preferences and the role of several factors (such as plant species, size and anthropopression level) that affect the beavers’ foraging in northern Poland. Woody plants along the river were measured and classified according to species in six 100 m-long transects that were characterized by a diversified human disturbance level. Ivlev’s electivity index was used to present the beavers’ preferences for various plant species and sizes, and the generalized linear model was used to assess the significance of studied factors in beavers’ browsing choices. Most popular in the beavers’ diets were willows (Salix), maples (Acer) and alder (Alnus), but only willows and maples were preferred. We noted a decrease in the beavers’ foraging preference in parallel to an increase in the shoot diameter; plants with a diameter below 10 cm were preferred. All factors included in the generalized linear model (GLM) were significant in shaping the beavers’ foraging choices. A negative correlation between the shoot diameter and the human disturbance level was found, but the species composition of the browsed woody plants was the same in each transect. Beavers’ foraging preferences, as observed in our study, were similar to those described in the literature and confirmed the role of woody species and their diameters in shaping the beavers’ diet. We also suggested the potential role of anthropopression in the shaping of the beavers’ foraging behaviors.